2005
DOI: 10.4049/jimmunol.175.8.5152
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Human Cysteinyl Leukotriene 1 Receptor Gene Structure

Abstract: The 5-lipoxygenase pathway has been strongly implicated in the pathogenesis of chronic inflammatory disorders, such as bronchial asthma and atherosclerosis. Cysteinyl leukotrienes (cysLTs), 5-lipoxygenase pathway products, are recognized now not only as important factors in asthmatic inflammation, but also as mediators of cell trafficking and innate immune responses. To study a role of cysLTs in inflammatory reactions we have characterized the gene structure of human cysteinyl leukotriene receptor type I (cysL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 42 publications
5
67
0
Order By: Relevance
“…We previously showed that in human PBMCs 2 alternative splice variants of CysLTR 1 can be detected. 23 Analysis of mRNA expression showed that CysLTR 1 transcript 1 is the major transcript detected in monocytes, with 20-to 40-fold higher levels than CysLTR 1 transcript 2 and CysLTR 2 . Also, functional data point to CysLTR 1 signaling as the major pathway in response to CysLTs because calcium signaling, gene expression, activation of p38 MAPK, and monocyte chemotaxis all were inhibited by the selective CysLTR 1 inhibitor MK571.…”
Section: Discussionmentioning
confidence: 97%
“…We previously showed that in human PBMCs 2 alternative splice variants of CysLTR 1 can be detected. 23 Analysis of mRNA expression showed that CysLTR 1 transcript 1 is the major transcript detected in monocytes, with 20-to 40-fold higher levels than CysLTR 1 transcript 2 and CysLTR 2 . Also, functional data point to CysLTR 1 signaling as the major pathway in response to CysLTs because calcium signaling, gene expression, activation of p38 MAPK, and monocyte chemotaxis all were inhibited by the selective CysLTR 1 inhibitor MK571.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, a T H 2 environment with IL-4 induced CysLTR1 expression and MCP-1 production in bronchial epithelial cells. Secretion of MCP-1 from IL-4 -primed A549 cells was further increased after stimulation with LTD 4 . The upregulation of CysLTR1 expression by IL-4 can be explained by a signal transducer and activator of transcription 6 element localized in its promoter region 4 that may promote the proinflammatory effects of CysLTs.…”
Section: Regulation Of Monocyte Chemoattractant Protein 1 By Cysteinymentioning
confidence: 91%
“…Secretion of MCP-1 from IL-4 -primed A549 cells was further increased after stimulation with LTD 4 . The upregulation of CysLTR1 expression by IL-4 can be explained by a signal transducer and activator of transcription 6 element localized in its promoter region 4 that may promote the proinflammatory effects of CysLTs. Increased production of MCP-1 in bronchial epithelial cells may promote infiltration of eosinophils, 5 which may lead to chronic inflammation in the asthmatic airway.…”
Section: Regulation Of Monocyte Chemoattractant Protein 1 By Cysteinymentioning
confidence: 91%
“…The 5ЈRACE was performed on total RNA extracted from HUVEC, HMVEC-L, human elutriated monocytes, THP-1, and U937 cells using the Gene Racer kit (Invitrogen Life Technologies), as previously described (20). The following CysLTR2 gene-specific primers were used: GSP1, 5Ј-CCAGGAAACGCACAACACTCAGCACG and GSP2 nested, 5Ј-GAT AGGGAGATGGATGGTTGCAAGGAC.…”
Section: Racementioning
confidence: 99%
“…Human CysLTR2 promoter fragments were cloned into pGL3-basic plasmid reporter vector (Promega) using the method previously described (20). A set of fragments up to 3012 bp long (numbers refer to the length of cloned promoter fragments with 3Ј end localized to position Ϫ43 in relation to 3Ј end of exon 1 as nt Ϫ1) of the identified CysLTR2 putative promoter region was amplified from human genomic DNA (Stratagene) by PCR with the following primers containing consensus sequences for KpnI and SacI restriction enzymes: p3012 F1, 5Ј-GACTAGGTCGGTACCTAC AGATTCAGAAGCAGGGAGTAGG and R1, 5Ј-GACTAGGTCGAGCT CCTATCTCTCCTGCCTTTC; p1305 F2, 5Ј-GACTAGGTCGGTACCTC CTTAGTTTCCATTTTTGGATTGTT and R1; p976 F3, 5Ј-GACTAGGT CGGTACCTTTATGGGCAGAACAAATGGAACT and R1; p339 F4, 5Ј-GACTAGGTCGGTACCTCTAAAGTGCTATGTGTGTAAGG and R1; p224 F5, 5Ј-GACTAGGTCGGTACCGGTTTCTTCTTTTTAGACATAGC FIGURE 1.…”
Section: Plasmid Constructionmentioning
confidence: 99%